2020
DOI: 10.1002/smll.202003485
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Design of Two‐Dimensional Oxide Nanosheets for Construction of Ultrathin Multilayer Nanocapacitor

Abstract: (LB) approach at room temperature which is verified by cross-sectional high-resolution transmission electron microscopy (HRTEM). The resultant MNCs demonstrate a high capacitance of 40-52 µF cm −2 and low leakage currents down to 10 −5-10 −6 A cm −2. Such MNCs also possess complimentary in situ robust dielectric properties under high-temperature measurements up to 250 °C. Based on capacitance normalized by the thickness, the developed MNC outperforms state-of-the-art multilayer ceramic capacitors (MLCC, ≈22 µF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The increase of ∼0.4 nm in each higher m member is a signature of the addition of one NbO 6 octahedron along the thickness. The nanosheets assembly via the LB method is a productive approach for ambient temperature construction of densely packed monolayer films on the atomic level smooth SrRuO 3 substrate . Therefore, we used the LB approach for deposition of closely assembled homologous perovskite nanosheets as monolayer films (Figure a–d) on the solid substrate and demonstrated that each film was atomically flat (roughness ∼0.3 nm) over a large area with minimum gaps and overlaps.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of ∼0.4 nm in each higher m member is a signature of the addition of one NbO 6 octahedron along the thickness. The nanosheets assembly via the LB method is a productive approach for ambient temperature construction of densely packed monolayer films on the atomic level smooth SrRuO 3 substrate . Therefore, we used the LB approach for deposition of closely assembled homologous perovskite nanosheets as monolayer films (Figure a–d) on the solid substrate and demonstrated that each film was atomically flat (roughness ∼0.3 nm) over a large area with minimum gaps and overlaps.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The nanosheets assembly via the LB method is a productive approach for ambient temperature construction of densely packed monolayer films on the atomic level smooth SrRuO 3 substrate. 28 Therefore, we used the LB approach for deposition of closely assembled homologous perovskite nanosheets as monolayer films (Figure 1a−d) on the solid substrate and demonstrated that each film was atomically flat (roughness ∼0.3 nm) over a large area with minimum gaps and overlaps. The LB deposition was repeated in an LbL manner for the assembly of homologous perovskite nanosheets to construct well-ordered nano-lamellar design multilayer/superlattice films.…”
Section: Resultsmentioning
confidence: 99%
“…Those layered perovskites have been reported as starting materials for monolayer transition metal oxide (TMO) nanosheets. A TMO nanosheet is an example of a two-dimensional (2D) nanomaterial, whose lateral size to thickness aspect ratios can reach 1,000–10,000. TMO nanosheets were studied as a building block for an electric/dielectric device with ultimate thickness, a superlattice with characteristic photoluminescence, and a multifunctional free-standing film with excellent flexibility. The strategy of using an interlayer cation-exchange reaction to reduce the electrostatic interaction between the perovskite layers and cationic layers has been successful for the delamination of a large variety of layered perovskites. In the case of Aurivillius-phase layered perovskites, however, the strong electrostatic interaction due to the high charge density of the perovskite layers must be overcome to achieve a high degree of delamination.…”
Section: Introductionmentioning
confidence: 99%
“…They can serve as multipurpose precursors for creating multilayer films, porous composites, and layered nanocomposites [33,[35][36][37][38]. The resulting nanolayers already show intriguing properties with potential uses in photoluminescence [39,40], catalysis [16,[41][42][43], and energy storage [44,45].…”
Section: Introductionmentioning
confidence: 99%